GENETIC ASSOCIATION AMONG MORPHOLOGICAL TRAITS OF ZEA MAYS SEEDLINGS UNDER SALT STRESS - Nawaz, A; Haseeb, A; Malik, HA; Ali, Q; Malik, A (Biological and Clinical Sciences Research Journal, 2020)
Zea mays is an important cereal crop which has been used by human from last thousands of years as grain crop. It is very sensitive for drought, heat, cold, salinity and heavy metals toxicity. For evaluating corn for salt stress we have conducted an experiment in the greenhouse of IMBB, University of the Lahore. Four maize genotypes were selected for our research work, viz., B-316, EV-1097Q, Raka-poshi and Sahiwal-2002 under the treatments of salt were kept as following: control, 0.2Molar NaCl, 0.5Molar NaCl, 0.7Molar NaCl and 1Molar NaCl. The selection of genotypes for high shoot and root length under treatments 0.5Molar NaCl, 0.7Molar NaCl may be fruitful for the improvement of crop production and productivity. It was found from results that the B-316 performed better under all stress treatments for seedling traits as compared with EV-1097Q and Sahiwal-2020 maize genotypes. The results showed that higher genetic advance and heritability was recorded for both root length and shoot length. The significant and positive correlation was recorded among root length, shoot length, root dry weight and shoot dry weight. The regression analysis showed that the higher contribution for shoot length was found for root length. It was concluded from our study that the selection of maize genotypes may be fruitful on the basis of root length and shoot length to improve grain yield under salt stress conditions.